Properties Comparison of Asphalt Cement and Multigrade Asphalt in Asphalt Concrete - Jetiyanonta, Kosintra; Witayakul, Watcharin (Agriculture and Natural Resources, 2001)
The engineering properties of multigrade asphalt compared with asphalt cement grade 60/70 were investigated and the performance of asphalt concrete was mixed between both binding materials and limestones. The results showed that the engineering properties of multigrade asphalt did not pass the specifications of Department of Highways. Multigrade asphalt had more sensitivity of penetration index than asphalt cement grade 60/70, and provided flexible performance after torsion, rheological behavior and torsional recovery better than asphalt cement, but had less ductility than that of asphalt cement. Additionally, the performance of asphalt concrete mixed with multigrade asphalt gave higher stability, flow and ratio of stability and flow than those mixed with asphalt cement grade 60/70. After compaction test, the samples mixed with multigrade asphalt gave higher tensile strength and modulus of elasticity than those mixed with asphalt cement grade 60/70 but had lower poisson’s ratio. Asphalt concrete mixed with multigrade asphalt also had greater strength index value and smaller rutting. Therefore, multigrade asphalt may be one of the alternative binders used for asphalt concrete design in highway construction if it had been notified of such use.